Trihoney ameliorates hypercholesterolemia-induced epididymal histopathological changes in male rabbits - Hamad Mohamed, Zenab; Ibrahim, Muhammad; Hamad Alfarisi, Hamad Abdulsalam; Abdul Wahab, Azantee Yazmie; Abd. Fuaat, Azliana; Che Mohamad, Che Anuar (University of Malaya, 2020)
Hypercholesterolemia has been linked to weight change and histopathological alteration of male reproductive organs. The epididymis was suggested to be an early target of lipid-related infertility and can be dramatically affected by excess intake of a high cholesterol diet. On the other hand, the interest has been increased towards the use of honey as a prophylactic and therapeutic agent for various diseases. Therefore, the purpose of this study is to investigate the effects of Trihoney (a mixture of Trigona, Mellifera and Tualang) on epididymal weight change and histopathological alterations in hypercholesterolemic male rabbits and compare its effects with atorvastatin. Forty-eight mature male New Zealand white rabbits were divided into 6 groups. Two groups received standard rabbit pellet with 0 and 0.6 g/kg/day of Trihoney respectively while the other four groups received 1% cholesterol diet with 0, 0.3, 0.6 g/kg/day of Trihoney, and 2 mg/kg/day of atorvastatin. After 12 weeks, the rabbits were sacrificed and the epididymides were harvested for evaluation of weight and histopathological changes. Administration of 1% cholesterol diet either alone or in combination with atorvastatin caused a significant reduction in the epididymal weight and epididymal atrophy. Supplementation of Trihoney particularly at the dose of 0.6 g/kg/day improved epididymal weight, regained the normal architecture of the epididymal histology and increased the number of mature sperm inside the tubules of the epididymis. Based on these results, Trihoney exhibited its potential health benefit as a protective agent against epididymal weight reduction and histopathological alterations in hypercholesterolemic rabbits. © 2020, University of Malaya. All rights reserved.